Norway : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes inflation in Norway with a view to shedding light on this surprising development and the possible near-term course of inflation, using statistical and econometric analyses. The paper reviews recent developments of monetary policy and inflation in Norway, applies statistical and econometric tools to identify factors influencing inflation, and describes the implications of the analysis for policymaking. Using data for six advanced small open economies explicitly targeting inflation, the paper examines empirically whether deviations of the exchange rate from their equilibrium levels systematically affect the conduct of monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet